Stress levels & coping strategies among university students in Universiti Malaysia Sarawak - Mansoor, Ajmal (2012)
University education is stressful and demanding. Stress may affect students' health and their academic performance. A student's life is subjected to different kinds of sressors, such as the pressure of academics with an obligation of success, uncertain future and difficulties envisaged for integration into the system. Coping strategies are specific efforts that individuals employ to manage stress. Positive coping strategies help reduce stress while use of drugs and alcohol to manage academis stress may worsen the situation. This study aimed to assess the levels of stress among undergraduate students and their coping strategies.